The Effects of the Intensity of the Unconditioned Stimulus on the Acquisition and Extinction of the Conditioned Emotional Response - Annau, Zoltan (My University, 1960)
The effects of intensity of the unconditioned stimulus (US) on the acquisition and extinction of the conditioned emotional response (CER) in rats were investigated. The US intensities studied were 0.28, 0.49, 0.85, 1.55, and 2.91 ma. Both acquisition and extinction of the CER were found to be monotonic functions of US intensity, with the higher US intensities producing more rapid acquisition and more resistance to extinction. The lowest shock intensity failed to produce suppression. The 0.49 ma. subjects typically showed a partial recovery of normal operant behavior after development of a fairly profound CER. The results were interpreted as consistent with the supposition that the CER is acquired in accordance with Pavlovian laws of classical conditioning.
Keywords: conditioned emotional response; unconditioned stimulus; acquisition; extinction